ISOLASI, SELEKSI DAN OPTTMASI PRODUKSI PROTEASE DARIBEBERAPAISOLAT BAKTERI - Naiola, Elidar; Widhyastuti, Nunuk (Research Center for Biology-Indonesian Institute of Sciences, 2002)
Thirty-seven out of sixty-one bacterial isolates from various sources of samples were screened for protease production. The isolate of ISO PL3 could produce the highest enzyme activity, and it was used as a standard bacterial strain in this observation. For any reason,we implemented ISO PL2 to study the optimum condition for producing bacterial protease. Result shows that the maximum protease activity was obtained in a medium containing 100 gram of rice brand in a liter tofu liquid waste. The optimum for incubation was 4- 6 days (agitation of 130 rpm at room temperature) and pH 5.0 - 6.0. After cultivating on this liquid medium, the maximum protease activity of the 2 ISO PL3 was 113,52 x 10 U/ml. From the studies on morphological and physiological characterization, it was indicated that ISO PL3 resemble with the species Bacillus macerans.